Amphisbaena uroxena Mott, Rodrigues, De Freitas and Silva 2008 (Squamata, Amphisbaenidae) shows sexual dimorphism in precloacal pores - Mott, Tamí; Rodrigues, Miguel Trefaut; de Freitas, Marco Antônio (Zootaxa, 2011)
In 2008, Mott, Rodrigues, De Freitas and Silva (Journal of Herpetology 42: 172) described as a new species Amphisbaena uroxena, characterized among other features by the presence of conic tubercles concentrated in a circle on the dorsal surface of the tail, an unique feature among South American amphisbaenids. At that time, based only on the three specimens of the type series, all without precloacal pores, they speculated that the absence of pores could be a sex-based difference. In fact, in other amphisbaenid species, the absence of pores in females has been either reported (A. dubia and A. heathi, Vanzolini 2002; A.hiata, Montero & Céspedez 2002) or noticed (A. anaemariae, observed by TM).